Effect of Fermentation Time on Molecular Structure and Physicochemical Properties of Corn Ballast Starch - Wei, Chunhong; Ge, Yunfei; Zhao, Shuting; Liu, Dezhi; Jiliu, Junlan; Wu, Yunjiao; Hu, Xin; Wei, Mingzhi; Wang, Yifei; Wang, Weihao; Wang, Lidong; Cao, LongKui (Frontiers in Nutrition, 2022)
To elucidate the effect of natural fermentation on the molecular structure and physicochemical properties of corn ballast starch, corn ballast was naturally fermented for 1-20 d and corn starch was obtained by alkali extraction. We investigated the effect of fermentation time on the surface morphology, crystalline structure, molecular weight of starch, starch chain length distribution, starch pasting, aging, solubility, and swelling properties of starch granules. The amylose content in corn ballast starch first decreased and then increased after natural fermentation, which followed the same trend as solubility. There were certain erosion marks on the surfaces of fermented corn ballast starch granules. The crystalline structure of corn ballast starch remained the same, i.e. a typical A-type crystalline structure, at different fermentation times; however, the intensities of diffraction peaks were different. The weight-average molecular weight of starch first increased and then decreased after fermentation. The content of low-molecular-weight starch (peak 3) decreased from 25.59% to 24.7% and then increased to 25.76%, while the content of high-molecular-weight starch (peak 1) increased from 51.45% to 53.26%, and then decreased to 52.52%. The fermentation time showed a negative correlation with the viscosity of starch, and the pasting temperature first increased, and then decreased. The results of this study can provide a theoretical basis and data support for technical control of the natural fermentation process of corn ballast and corn starch food processing.